2014
DOI: 10.1016/j.ijppaw.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Wild and synanthropic reservoirs of Leishmania species in the Americas

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
211
0
36

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(252 citation statements)
references
References 136 publications
5
211
0
36
Order By: Relevance
“…Currently, L. braziliensis is considered a dermotrophic species in the human leishmaniasis disease complex, with isolation and detection of this species in the viscera only in cases of immunologically compromised patients GONTIJO et al, 2002). In wild and synantropic animals (considered potential reservoirs for L. braziliensis), such a distinction regarding tissue tropism does not exist (ROQUE et al, 2010;ROQUE & JANSEN, 2014), and the parasite may be detected in many organs. In dogs, this species has only been detected in cutaneous lesions (MADEIRA et al, 2005;DANTAS-TORRES, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, L. braziliensis is considered a dermotrophic species in the human leishmaniasis disease complex, with isolation and detection of this species in the viscera only in cases of immunologically compromised patients GONTIJO et al, 2002). In wild and synantropic animals (considered potential reservoirs for L. braziliensis), such a distinction regarding tissue tropism does not exist (ROQUE et al, 2010;ROQUE & JANSEN, 2014), and the parasite may be detected in many organs. In dogs, this species has only been detected in cutaneous lesions (MADEIRA et al, 2005;DANTAS-TORRES, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular characterization indicated that Brazilian H. canis was closely related to isolates from Japan, presented 99% nucleotide identity with isolates from Israel and was found to be distantly related to H. americanum (RUBINI et al, 2005). In the following years, canine hepatozoonosis has also been described in several Brazilian regions (RUBINI et al, 2008;MIRANDA et al, 2014;GONÇALVES et al, 2014;RAMOS et al, 2015;DEMONER et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…For L. panamensis and L. guyanensis, an important reservoir has been identiied to be Choloepus hofmanni sloths [36].…”
Section: Study Of Reservoirsmentioning
confidence: 99%
“…and are considered as a potential reservoir due to its broad distribution throughout Latin America, in both rural and urban areas (32)(33)(34).…”
Section: On the Other Hand Possums (Didelphis Marsupialis) Have Beenmentioning
confidence: 99%